Tradisi hajat lembur sebagai media berbagi pengetahuan masyarakat Tatarkarang Jawa Barat - Ninis Agustini Damayani; Encang Saepudin; Neneng Komariah (Jurnal Kajian Informasi dan Perpustakaan, 2020)
The process of sharing knowledge in the 'hajat lembur' tradition requires knowledge management to support the continuity of the tradition. The research aimed to discover the steps of sharing knowledge on 'hajat lembur' traditions. The method used a qualitative case study approach. Data collection was through interviews, discussions, observations, and literature studies. The data validity test process used data triangulation and source triangulation. Data analysis was performed descriptively through the stages of reduction, presentation, and concluding. The data source consisted of six people: two community and religious leaders, three people managing Saung Budaya Tatarkarang, and one government official. Results showed knowledge sharing activities in the process of 'hajat lembur' tradition is a form of gratitude as well as a medium in building human relations with humans, humans with nature, and humans with God, consisted of four stages: socialization, internalization, combination, and externalization. Socialization is in the form of village elders' information delivery about the concept of 'hirup anu hurip' by creating a harmony of life among people, between humans with nature, and humans with their gods. Internalization process, received knowledge is processed and stored in the memory of each individual. Combination process, each member of the community reconfigures explicit knowledge by sorting, classifying, and developing. Externalization, the knowledge in one's mind is conveyed to others by certain media. In conclusion, the Tatarkarang community keep a harmony of life through relations with humans, humans with nature, and humans with God.